Characteristics, Classification, and Prevention of Child Maltreatment Fatalities. Issue 1 (1st January 2017) - McCarroll, James E.; Fisher, Joscelyn E.; Cozza, Stephen J.; Robichaux, Renè J.; Fullerton, Carol S.
ABSTRACT: Background: Preventing child maltreatment fatalities is a critical goal of the U.S. society and the military services. Fatality review boards further this goal through the analysis of circumstances of child deaths, making recommendations for improvements in practices and policies, and promoting increased cooperation among the many systems that serve families. The purpose of this article is to review types of child maltreatment death, proposed classification models, risk and protective factors, and prevention strategies. Methods: This review is based on scientific and medical literature, national reports and surveys, and reports of fatality review boards. Findings: Children can be killed soon after birth or when older through a variety of circumstances, such as with the suicide of the perpetrator, or when the perpetrator kills the entire family. Death through child neglect may be the most difficult type of maltreatment death to identify as neglect can be a matter of opinion or societal convention. These deaths can occur as a result of infant abandonment, starvation, medical neglect, drowning, home fires, being left alone in cars, and firearms. Models of classification for child maltreatment deaths can permit definition and understanding of child fatalities by providing reference points that facilitate research and enhance clinical prediction. Two separate approaches have been proposed: the motives of the perpetrator and the circumstances of death of the child victim. The latter approach is broader and is founded on an ecological model focused on the nature and circumstances of death, child victim characteristics, perpetrator characteristics, family and environmental circumstances, and service provision and need. Many risk factors for maternal and paternal filicide have been found, but most often included are young maternal age, no prenatal care, low education level, mental health problems, family violence, and substance abuse. Many protective factors can be specified at the individual, family, and community level. Early interventions for children and families are facilitated by the increased awareness of service providers who understand the risk and protective factors for intentional and unintentional child death. Discussion/Impact/Recommendations: There is currently no roadmap for the prevention of child maltreatment death, but increased awareness and improved fatality review are essential to improving policies and practices. Prevention strategies include improving fatality review recommendations, using psychological autopsies, serious case reviews, and conducting research. We recommend a public health approach to prevention, which includes a high level of collaboration between agencies, particularly between the military and civilian. The adoption of a public health model can promote better prevention strategies at individual, family, community, and societal levels to address and improve practices, policies, and public attitudes and beliefs about child maltreatment. The process of making recommendations on the basis of fatality review is important in terms of whether they will be taken seriously. Recommendations that are too numerous, impractical, expensive, lack relevance, and are out of step with social norms are unlikely to be implemented. They can be helpful if they are limited, focused, lead to definitive action, and include ways of measuring compliance.